Demographic and clinical characteristics of recurrent rhegmatogenous retinal detachment cases treated with retinectomy - BAĞATUR VURGUN, ELİF (My University, 2021)
Purpose: To report the demographic and clinical characteristics of recurrent rhegmatogenousretinal detachment cases treated with retinectomy.Setting: Vitreoretinal Surgery Unit, Ophthalmology Department, Marmara University PendikTraining and Research Hospital, Istanbul, Turkey.Methods: This retrospective, noncomparative, interventional case series included 15 eyes of15 patients that had undergone retinectomy for recurrent rhegmatogenous retinal detachment.We assessed demographic and clinical features, including age, sex, follow up time, best-corrected visual acuity (BCVA, logMAR), the time between symptoms and the surgery,macula status (on and off), type of first surgery, number of surgeries before retinectomy,proliferative vitreoretinopathy (PVR) grade, the operative technique (including relaxingretinectomy, intraocular tamponade, and laser photocoagulation), silicone oil tamponadeduration, retinal status with silicone oil tamponade, the period between silicone oil removal,and recurrent detachment.Results: Of the 15 patients included (74% male and 26% female), the mean±SD age was56.5±8.7 years (range, 40–75). The mean follow-up time was 16.7±10.4 months (range6–48), and the mean preoperative BCVA was 1.64±0.8 logMAR. The time betweensymptoms and the first surgery was 18.6±20.3 days (range, 1–103). The PVR grades of thecases were PVR-A in two (13.3%), PVR-B in six (40.0%), and PVR-C in seven (46.7%)patients. The macular status of the patients was macula-on in four (26,7%) and macula-off ineleven (73,3%) patients. Five patients (33.3%) received a 360-degree laser retinopexy in thefirst surgery. Five patients (33.3%) had recurrent detachment under silicon oil tamponade,while the remaining ten patients (66.7%) had recurrent detachment after silicone oil removal.The time between silicone oil removal and detachment recurrence was 95.1±99.4 days(range, 21–330). The mean operation count before retinectomy was 1.53±1.1 (range, 1–5).All patients underwent a minimum 100-degree retinectomy at the last surgery, and the retinaremained attached with silicone oil tamponade.Conclusion: Recurrent detachments can also be seen under silicone oil tamponade.Retinectomy may be effective in achieving anatomical success in recurrent detachments.
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; Clinical Medicine (MED); CLINICAL MEDICINE